Kajian Potensi Gua Pandan sebagai Objek Geowisata Lampung Timur - Rinda Ermana; Rezky Ariya Dwiguna; Hesti Hesti; Rahmi Mulyasari (Jurusan Fisika, Universitas Bangka Belitung, 2022)
Indonesian tourism has developed in various sectors and regions in Indonesia. Various types of tourism have been presented in modern, traditional and rural forms. One of them is related to the development of geotourism in Indonesia. Geotourism has benefits, namely the welfare of the people who live around it, encouraging local people to participate in maintaining and developing geotourism, realizing sustainable tourism development, giving a distinct impression and experience for every tourist who comes. Pandan Cave is one of the geosites in Giri Mulyo, East Lampung. The Pandan Cave area is included in the Sukadana Lava lithology unit (Qbs). Pandan Cave in geomorphological studies includes structural landforms formed as a result of endogenous processes, in the form of lifting, folding, and faulting. This endogenous force is constructive. Pandan Cave has geotourism potential because of its unique geology, the various rock forms that make up Pandan Cave and its morphology are interesting things for tourists to study geology. In addition, the location of Pandan Cave which is in the plantation of residents close to the village, makes this tourist attraction an interesting place to visit.